The Latin American common market - United Nations (New York : United Nations, Dept. of Economic and Social Affairs, 1959)
This volume has been divided into five main sections which, being closely inter-related, impart a certain amount of unity although each of the component documents is self-contained.
"United Nations publication. Sales no.: 59.II.G.4."
osc 29/08/2018
Loans
Keywords: Labor productivity; Cotton manufacture; Latin America